Burzenie i tworzenie schematów inicjacyjnych w filmach Felliniego - Grochowiak, Anna (Załącznik Kulturoznawczy, 2022)
The period of going through puberty for Fellini himself was turbulent and unusual. In various interviews, the director gives his own memories from that time a different narrative – he changes the “testimonies” and modifies the facts. Equally inconsistent with culturally and socially created initiation models are the fates of the protagonists in his films, who go through the period of “growing up” and “puberty” at different ages and in different ways, usually contradicting stereotypical images, however not always. The director seems to use well-known patterns and show them in a crooked mirror or transplant them onto non-obvious grounds. The protagonists are often shown on the verge of change, facing the problem of crossing a specific line and reaching “maturity” (this concept also encapsulates various values). In this essay I examine the aspects of liminality and initiation in Fellini’s films, using examples such as La strada, 8 and ½ and Amarcord as well as the broad context of all of his works and his biography.